Evaluating the Usability of Authoring Environments for Serious Games. (August 2017) - Slootmaker, Aad; Hummel, Hans; Koper, Rob
Background . The EMERGO method and online platform enable the development and delivery ofscenario-based serious games that foster students to acquire professional competence. One of the main goals of the platform is to provide a user-friendlyauthoring environment for creating virtual environments where students can perform authentic tasks. Aim . We present the findings of an in-depth qualitative case study of the platform'sauthoring environment and compare our findings on usability with those found for comparable environments in literature. Method . We carried out semi-structured interviews, with two experienced game developers who have authored a game for higher education, and a literature review of comparable environments. Findings . The analysis shows that theusability of theauthoring environment is problematic, especially regardingunderstandability andlearnability, which is in line with findings of comparable environments. Other findings are that authoring is well integrated with the EMERGO method and thatfunctionality andreliability of the authoring environment are valued. Practical implications . The lessons learned are presented in the form of generalguidelines to improve theunderstandability andlearnability ofauthoring environments forserious games .